2017
DOI: 10.1259/bjr.20170165
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effects of chemoradiotherapy in pursuit of optimal treatment of locally advanced unresectable pancreatic cancer

Abstract: The results of this study suggested that CRT is clinically effective in improving survival, particularly in association with the resultant possibility of curative resection. Advances in knowledge: The best treatment strategy for patients with locally advanced unresectable pancreatic cancer is the subject of considerable debate, and CRT is only recommended if cancer has only grown around the pancreas without any distant metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 36 publications
2
10
1
Order By: Relevance
“…Our retrospective data indicate that regardless of neoadjuvant chemotherapy regimen, approximately 25% of patients had the chance to undergo surgical exploration with curative intent, among which 75% were resected, leading to a final patient ratio of 1:5 for surgical resection versus no resection in LAPC. This resection rate seems to be low compared with previous retrospective studies, 27,28,33,34 and we can acknowledge 2 distinct factors for this difference: (1) borderline resectable PDAC patients were not part of the studied cohort (historically the resection rate for these patients in our institution is 65%), and (2) all LAPC patients who presented at PMDC were included in the initial pool, including those who did not receive neoadjuvant chemotherapy, or progressed early in the course of their disease. Most importantly however, surgical resection in LAPC patients was associated with an additional survival advantage that was comparable to their resected stage I/II counterparts.…”
Section: Discussioncontrasting
confidence: 57%
“…Our retrospective data indicate that regardless of neoadjuvant chemotherapy regimen, approximately 25% of patients had the chance to undergo surgical exploration with curative intent, among which 75% were resected, leading to a final patient ratio of 1:5 for surgical resection versus no resection in LAPC. This resection rate seems to be low compared with previous retrospective studies, 27,28,33,34 and we can acknowledge 2 distinct factors for this difference: (1) borderline resectable PDAC patients were not part of the studied cohort (historically the resection rate for these patients in our institution is 65%), and (2) all LAPC patients who presented at PMDC were included in the initial pool, including those who did not receive neoadjuvant chemotherapy, or progressed early in the course of their disease. Most importantly however, surgical resection in LAPC patients was associated with an additional survival advantage that was comparable to their resected stage I/II counterparts.…”
Section: Discussioncontrasting
confidence: 57%
“…So far, several articles related to CS for UR-PC patients have been reported. [8][9][10][11][12][13][14][15][16] Our results in this study may be the best among these previous articles. These values seemed to indicate the possibility of prognostic improvement effect in CS for patients with UR-PC to a certain extent.…”
Section: Discussionsupporting
confidence: 56%
“…This surgical strategy is called 5 "conversion surgery (CS)." 6,7 Several articles have also been reported for CS in patients with unresectable PC (UR-PC), [8][9][10][11][12][13][14][15][16] and its prognostic effect to CS have been mentioned. Hereafter, because of the remarkable progress of NST, candidates with UR-PC for CS is expected to increase.…”
Section: Introductionmentioning
confidence: 99%
“…Conversion surgery represents a new therapeutic strategy which may improve short- and long-term outcomes of patients with UR-PDAC. Several articles have reported the utility of CS in such patients, as well as the positive effects on prognosis [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. In the present study, the rate of CS among patients with UR-LA and UR-M was similar to that reported previously [ 25 ].…”
Section: Discussionmentioning
confidence: 99%